Strategi Peningkatan Literasi Digital Masyarakat dalam Mencegah Penyebaran Hoaks di Era Digital - Bambang Suprianto (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The community service program carried out in RT 038, Sukarami Village, aimed to enhance the digital literacy of residents to prevent the spread of hoaxes. The main issue faced was the low awareness and skills of residents in verifying digital information, leading to a high spread of hoaxes. The methods used in this program included initial surveys, program planning meetings, digital literacy education and training, as well as discussion and evaluation sessions. The results of the program showed a significant increase in residents' digital literacy, with 80% of respondents able to verify information after the program. There was a decrease in the spread of hoaxes, from 60% before the program to 20% after the program. Residents also became more critical and inclusive in receiving and disseminating information, and more vigilant against potential online threats. Thus, this program successfully built a stronger and more resilient community in facing information challenges in the digital era.